2021
DOI: 10.3389/fonc.2021.696881
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: EGFR-Positive Early-Stage Lung Adenocarcinoma Transforming to Squamous Cell Carcinoma After TKI Treatment

Abstract: The histological transformation from epidermal growth factor receptor (EGFR)-mutated adenocarcinoma (ADC) to squamous cell carcinoma (SCC) after tyrosine kinase inhibitor (TKI) treatment is rare. We present a case of a patient who transitioned from early-stage primary lung ADC with partial squamous differentiation, EGFR mutation and amplification, to adrenal gland metastasis as SCC with EGFR amplification disappearance 115-months after surgery, during which gefitinib and local radiotherapy were utilized for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Transformation to lung squamous cell carcinoma (SCC). In recent years, several cases of transformation of EGFR-mutated NSCLC to SCC have been reported (117)(118)(119)(120)(121), and some reports indicate the association between the T790M mutation and SCC transformation (122,123). As this morphological transformation is rare, the mechanism is unclear, although it has been shown that it may be related to changes in the PI3K/AKT/mTOR pathway during EGFR-TKI therapy (124).…”
Section: Histological Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transformation to lung squamous cell carcinoma (SCC). In recent years, several cases of transformation of EGFR-mutated NSCLC to SCC have been reported (117)(118)(119)(120)(121), and some reports indicate the association between the T790M mutation and SCC transformation (122,123). As this morphological transformation is rare, the mechanism is unclear, although it has been shown that it may be related to changes in the PI3K/AKT/mTOR pathway during EGFR-TKI therapy (124).…”
Section: Histological Transformationsmentioning
confidence: 99%
“…For patients with drug-resistant lung SCC, the prognosis is usually poor, and the mOS is only ~3.5 months ( 120 ). It is difficult to choose follow-up treatments due to the low incidence; Liao et al ( 121 ) reported the case of a patient who received almonertinib for 6 months after detection of the SCC phenotype. At the time of writing the study, the patient was continuing almonertinib monotherapy and the disease was stable.…”
Section: Drug Resistance Mechanisms and Progress In The Use Of First-...mentioning
confidence: 99%